THE TRANSLATOR’S VOICE AS A READER’S RESPONSE IN THE ARABIC TRANSLATION NOVEL OF 'LASKAR PELANGI' - Shinta Fitria Utami (Leksema: Jurnal Bahasa dan Sastra, 2024)
This article aims to trace the translator’s voice as a response to the novel Laskar Pelangi through its translation entitled Asākiru Qawsi Quzah. This research adopts a descriptive qualitative approach. The research data consist of words, phrases, and sentences from the novel in the source language, which is Laskar Pelangi and the novel in the target language, which is Asākiru Qawsi Quzah. Data collection is carried out through non-participant observation and note-taking methods. Units of the source language are compared with units of the target language. Then, the recently generated narrative segments by the translator are analyzed using literary reception theory, through intertextual method, as a reference to uncover the translator’s response, as a reader, to the novel Laskar Pelangi. Furthermore, data are presented using both formal and informal techniques. The research findings indicate that the translator responds to the novel by emphasizing poverty disparities represented by SD Muhammadiyah Gantong, its teachers, and students. SD Muhammadiyyah Gantong lacks adequate facilities, knowledge, and human resources.